Modified Newton Kantorovich Methods for Solving Microwave Inverse Scattering Problems - Agung Tjahjo Nugroho (Jurnal ILMU DASAR, 2009)
The Modified Newton-Kantorovich method (MNK) was formulated due to the limitation of The Newton-Kantorovich method (NK) in reconstructing the imitation of bone muscle and fat object. It was sensitive to contrast and cell size. In this research MNK and NK methods were applied to reconstruct the dielectric properties distribution of homogeneous and inhomogeneous objects from simulated scattered field dataset to know how the results of image reconstruction using both methods were. The results revealed that the MNK method was more flexible than the NK one.